2019
DOI: 10.3390/md17030162
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Phlorotannins Extraction from Fucus vesiculosus and Evaluation of Their Potential to Prevent Metabolic Disorders

Abstract: Phlorotannins are phloroglucinol-based phenolic compounds, occurring particularly in brown macroalgae, that have been recognized for their promising bioactive properties. In this study, the extraction of phlorotannins from Fucus vesiculosus was evaluated with particular emphasis on the influential parameters, including the solvent concentration, solvent-solid ratio, extraction temperature and extraction time, using a single-factor design followed by a Box-Behnken design. The maximum total phlorotannin content,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
148
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(164 citation statements)
references
References 57 publications
(87 reference statements)
16
148
0
Order By: Relevance
“…Fucus vesiculosus is a brown alga with prominent antidiabetic activities. According to the ultra-high-pressure liquid chromatography coupled to mass spectrometry (UHPLC-MS) analysis, the ethyl acetate fraction of Fucus vesiculosuswas reported to have phlorotannins such as fucols, fucophlorethols, fuhalols, fucofurodiphlorethol, fucofurotriphlorethol, and fucofuropentaphlorethol which showed a promising antidiabetic activity through the inhibitory activity of α-glucosidase (IC 50 : 0:82 ± 0:05 μg/ml: acarbose IC 50 : 206:6 ± 25:1 μg/ml) and α-amylase (IC 50 : 2:8 ± 0:3 μg/ml: acarbose IC 50 : 0:7 ± 0:2 μg/ml) enzymes [36]. In addition to the phlorotannins, Fucus vesiculosus produce fucoidans and Shan et al [37] evaluated the α-glucosidase inhibitory activity of fucoidan extracted from a brown alga Fucus vesiculosus and was reported to have the highest α-glucosidase inhibitory effect with IC 50 of 67.9 μg/ml compared to the standard drug acarbose (IC 50 :1000 μg/ml).…”
Section: Inhibitory Activity Of α-Amylase and α-Glucosidasementioning
confidence: 99%
“…Fucus vesiculosus is a brown alga with prominent antidiabetic activities. According to the ultra-high-pressure liquid chromatography coupled to mass spectrometry (UHPLC-MS) analysis, the ethyl acetate fraction of Fucus vesiculosuswas reported to have phlorotannins such as fucols, fucophlorethols, fuhalols, fucofurodiphlorethol, fucofurotriphlorethol, and fucofuropentaphlorethol which showed a promising antidiabetic activity through the inhibitory activity of α-glucosidase (IC 50 : 0:82 ± 0:05 μg/ml: acarbose IC 50 : 206:6 ± 25:1 μg/ml) and α-amylase (IC 50 : 2:8 ± 0:3 μg/ml: acarbose IC 50 : 0:7 ± 0:2 μg/ml) enzymes [36]. In addition to the phlorotannins, Fucus vesiculosus produce fucoidans and Shan et al [37] evaluated the α-glucosidase inhibitory activity of fucoidan extracted from a brown alga Fucus vesiculosus and was reported to have the highest α-glucosidase inhibitory effect with IC 50 of 67.9 μg/ml compared to the standard drug acarbose (IC 50 :1000 μg/ml).…”
Section: Inhibitory Activity Of α-Amylase and α-Glucosidasementioning
confidence: 99%
“…The extraction of Fucus vesiculosus with acetone:water (70:30, v/v) obtained a higher content of soluble phlorotannins than with other solvents or mixtures [79,80]; this is one of the most frequently used extraction solvent mixtures in the studies regarding phenolic compounds from macroalgae [35,60,70]. Catarino et al optimized the acetone concentration (in a range from 30% to 70% (v/v)) in order to maximize the TPhC of Fucus vesiculosus acetone:water extracts, reaching a maximum at 67% of acetone [9]. Additionally, in a scale-up perspective, the benign character of acetone has been up and coming in the increasing demand in the last years to achieve efficient extraction methodologies with a reduction, or an absence, of unsafe organic solvents consumption.…”
Section: Solvent Selectionmentioning
confidence: 99%
“…Actually, the use of higher extraction temperatures has been described to promote the oxidation of phenolic compounds [53]. Catarino et al demonstrated that the highest TPhC of Fucus vesiculosus extracts is obtained at 25 • C, in a studied range between 15 and 50 • C [9]. Notwithstanding, other authors have verified a positive effect of the extraction temperature on the phlorotannins recovery, namely in Eisenia bicyclis [38] and Macrocystis pyrifera [69], for which the best temperatures were reported to be 80 and 55 • C, respectively.…”
Section: Conventional Solid-liquid Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments were carried out by varying one condition at a time [48]. First, the carbon source (sucrose) was set to five concentration gradients (10-50 g L −1 ), and GBacillus-9 was cultured in M9 culture media for 10 h at 37 • C. Next, the antimicrobial ability was detected using the inhibition zone method to find the optimal concentration of the carbon source.…”
Section: Single-factor Experiments Designmentioning
confidence: 99%